GAME TECHNOLOGIES IN TEACHING - Toshmukhammedova Gulnoza Zayniddinovna; Nasimova Muattar Khasanovna (Galaxy International Interdisciplinary Research Journal, 2023)
Activating students on the basis of the use of game technologies and constitutes an accelerating activity. According to the studies of scientists, play is combined with work and study is one of the main types of activity. According to psychologists, play activity is psychological mechanisms of self-expression of the individual, stability of his place in life, self-management, fundamental to realizing one’s potential based on needs. The game is aimed at mastering and recreating social experiences. It is defined as a type of activity in situations and a person’s own behavior. Here management is formed and improved.